Prevalence Of Parafunctional Habits And Temporomandibular Disorder Symptoms In Young Individuals Reporting To Watim Dental Hospital - Aleshba Saba Khan; Aleeza Sana; Zarah Sufian; Ammarah Afreen; Asma Shakoor; Eruj Shuja (Journal of Rawalpindi Medical College)
Objective: This study aims to identify the prevalence of parafunctional habits and common symptoms of temporomandibular disorders in young individuals reporting to the Watim Dental College